Prolonging the antibacterial activity of nanosilver-coated membranes through partial sulfidation. Issue 9 (5th August 2020) - Barrios, Ana C.; Carrillo, Dianne; Waag, Tyson R.; Rice, Douglas; Bi, Yuqiang; Islam, Rafiqul; Perreault, François
Abstract : Silver sulfidation in nanosilver-coated membranes slows down silver release and increase biofouling resistance without affecting the membrane's functionality. Abstract : Biofouling is a major issue in membrane-based water treatment because it shortens membrane life and decreases the permeate flux. Silver, a known biocide, is often used for in situ formation of silver nanoparticles (Ag NPs) on membranes for biofouling mitigation. However, Ag NPs dissolve quickly in water, limiting their effectiveness over long periods of time. This study focuses on the modification of silver-functionalized reverse osmosis (RO) membranes with different concentrations of Na2 S (10 −1, 10 −3, and 10 −5 M) to identify the degree of sulfidation that limits Ag release while preserving the antibacterial effect. Sulfidized membranes decreased Ag release by >85% depending on the extent of sulfidation. Antibacterial activity was assessed using Pseudomonas aeruginosa and E scherichia coli . Results showed the highest inactivation at 73% for P. aeruginosa and 57% for E. coli for 10 −5 and 10 −3 M Na2 S-treated membranes, respectively, while the more sulfidized membrane treated with 10 −1 M Na2 S treatment had the lowest antibacterial effect. Moreover, when tested in a dynamic cross-flow RO system for 24 h, the flux declined by 24% for the Ag NPs and by 23%, 17%, and 19% as the extent of sulfidation increased. Additionally, the Ag remaining on the membrane was higher for the highest sulfidized membrane with 519 ng cm −2 . Therefore, retention of the silver coating over time appears to be more important for biofilm control in RO systems than high antibacterial activity. Both 10 −5 M and 10 −3 M Na2 S-treated membranes had the best balance between reduced Ag release rate and effective antibacterial and anti-biofouling performance, respectively.